ESMO Consensus Guidelines for management of patients with colon and rectal cancer. A personalized approach to clinical decision making - (:unkn) unknown (ELSEVIER, 2012)
Colorectal cancer (CRC) is the most common tumour type in both sexes combined in Western countries. Although screening programmes including the implementation of faecal occult blood test and colonoscopy might be able to reduce mortality by removing precursor lesions and by making diagnosis at an earlier stage, the burden of disease and mortality is still high. Improvement of diagnostic and treatment options increased staging accuracy, functional outcome for early stages as well as survival. Although high quality surgery is still the mainstay of curative treatment, the management of CRC must be a multi-modal approach performed by an experienced multi-disciplinary expert team. Optimal choice of the individual treatment modality according to disease localization and extent, tumour biology and patient factors is able to maintain quality of life, enables long-term survival and even cure in selected patients by a combination of chemotherapy and surgery. Treatment decisions must be based on the available evidence, which has been the basis for this consensus conference-based guideline delivering a clear proposal for diagnostic and treatment measures in each stage of rectal and colon cancer and the individual clinical situations. This ESMO guideline is recommended to be used as the basis for treatment and management decisions.
Keywords: METASTATIC COLORECTAL-CANCER; CAPECITABINE PLUS OXALIPLATIN; RANDOMIZED PHASE-III; ANGIOGENESIS INHIBITOR BEVACIZUMAB; GROWTH-FACTOR RECEPTOR; LIVER-ONLY METASTASES; GENE MUTATION STATUS; LONG-TERM SURVIVAL; 1ST-LINE TREATMENT; ADJUVANT CHEMOTHERAPY